THE INFLUENCE OF BALANCING FUNDS AND LOCALLY-GENERATED REVENUE ON ECONOMIC GROWTH IN SOUTH SUMATRA PROVINCE IN 2014-2018 - Novie Al Muhariah; Ali Akbar; Rangga Agusta Wijaya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study discusses the influence of balancing funds and locally generated revenue on economic growth in South Sumatra Province in 2014 - 2018. The analytical method used is the Multiple Linear Regression using the help of the program eviews 10. The results of the calculation show that: (a) partially the Balancing Fund variable (X1) has a significant influence on economic growth in South Sumatra and locally generated revenue (X2) has a significant influence on economic growth in South Sumatra. Then, they are tested to do together it is known that both the Balancing Fund (X1) and locally generated revenue (X2) together have a significant influence on economic growth in South Sumatra. (b) The value of the coefficient of determination (Adjusted R Square) is 0.99, it shows that 99% fluctuations in economic growth in South Sumatra are influenced by the Balanced Fund (X1) and locally generated revenue (X2) while the remaining 0,01% is influenced by variables other than variables in this study such as local expenditure and others